Global Longitudinal Strain May Be the One that Appropriately Identifies Candidates of ICD Implantation - Mohammad Hossein Nikoo; Mohammad Zarrabi; Alireza Moaref; Iman Razeghian-Jahromi (Cardiology Research and Practice)
Hypertrophic cardiomyopathy (HCM) significantly contributes to an elevated risk of sudden cardiac death. Primary prevention is implemented by using an implantable cardioverter defibrillator (ICD). However, all of the HCM patients do not really need ICD therapy. Providing a superior index for ICD indication compared with the current indices like ejection fraction is essential to differentiate high-risk patients efficiently. The present study assessed the potential of global longitudinal strain (GLS) for the differentiation of HCM patients based on their need for ICD shocks. Patients with HCM were considered in four defined centers between March and June 2021. Those with previous ICD implantation or current candidates for ICD therapy were included in the study. Participants were subjected to speckle-tracking echocardiography, and GLS as well as some other echocardiographic parameters were recorded. Afterwards, data from implanted ICDs were extracted. Patients who received ICD shocks (appropriate) due to ventricular tachycardia (VT)/ventricular fibrillation (VF) were categorized in group A. The remaining patients were constituted group B who received inappropriate shocks, i.e., other than VT/VF. Overall, 34 patients were found eligible to participate with a mean age of 62 ± 16.1 years including 64.7% of males. Among a variety of echocardiographic parameters, GLS was the sole one that was significantly higher in group A compared with that in group B. Our findings revealed that only GLS could predict fatal arrhythmias. To substantiate, the odds of VT were raised by 43% with a single increase in GLS unit. GLS showed the highest accuracy for ICD indication among HCM patients and, therefore, could be a solid and early criterion to predict the incidence of life-threatening arrhythmias. In this regard, identifying appropriate HCM patients with respect to their need for ICD therapy is feasible.